Ekonomi Keuangan Islam Dalam Konsep Al-Mashlahah Al-Mursalah - Suparmin, Sudirman (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2020)
Economic activity has existed since the time of the Prophet Muhammad. The basic foundation has actually been made with his own practice as a trader in his youth, besides al-Quran and al-Al-Sunnah also mention the limits of economic activity. In line with the increasingly widespread development of Muslims, various economic model activities have also emerged, so that sometimes it is not uncommon to find activities that develop in society that were never carried out during the time of the Prophet Muhammad and in the text we also do not find in the Al-qur’an or al-Sunnah. But on the basis of human needs, these activities are justified on the basis of the method of al-Mashlahaht. This is because the law of Allah SWT always depends on the increase of His Supremacy. Basic economic methods al-ibahah (allowed) to do so long as there is no argument that prohibits it. What the companions of the Prophet (PBUH) did like Abu Bakr, Umar ibn Khattab was not uncommon based on al-Mashlahah.